TÉTANO: uma abordagem em historias em quadrinhos (HQs) sobre o ensino do tétano nas aulas de ciências naturais - TENÓRIO, Kesy dos Santos (2024)
This work aims at verifying course completion as Comics (comics) can assist the process of teaching / learning tetanus. The Comics have been an alternative teaching / learning proven effective in several studies, and its own code of training and used universal language has influenced the cultural education of several generations. Emphasized, the present study Completion of the course aims at using history as a tool in teaching Comic tetanus. Thus, it was built a comic strip that addressed regarding tetanus and was distributed with the elementary students for the students' understanding of prior tetanus and post application of comics could be analyzed. As a specific purpose, we propose to analyze the comic strip presented to students caused them to understand the main features of tetanus, and the means of prevention and treatment. Characterization of tetanus, acute infectious disease, not contagious, resulting binomial interruption of skin / mucous and infection by Clostridium tetani. Life Cycle: The average incubation period is 10 days, ranging from 24 hours to 30 days. Some cases reach months. Prevention: according to the World Health Organization (WHO) tetanus vaccine when guaranteed its production, storage, application, full doses of the vaccine, as recommended by the immune response and vaccine regimen. When all these factors occur, its effectiveness is around 99%. Type of research: A qualitative approach was chosen, and the type of research was the field study at a school of elementary schools in the urban area of the municipality of Breves- PA. Data collection questionnaire with closed questions applied with 22 elementary school students. Search results: the survey results show that after applying the comic book to the students of the 6th year of elementary school, they seized knowledge about tetanus. It is noteworthy that by bringing the comic book to the students, they were willing to be seizing on tetanus from reading the comic. In that sense, I can say that after the students read the comic, they showed they had seized more about tetanus, as well as the means for its prevention.